Executive intelligence : what all great leaders have - Menkes, Justin (New York : Collins, 2005)
Based on eight years of research on intelligence tests and cognitive skills, the author reveals the set of aptitudes that all brilliant leaders share. Dr. Justin Menkes verified these findings through hundreds of interviews with senior executives, including thirty of the most celebrated CEOs in the world. Menkes discovered that just as great mathematicians share an exceptional facility for skills such as computation and deductive reasoning, great managers also have a certain set of cognitive skills that are at the heart of business acumen. What star leaders do is not magic. Their accomplishments are made possible by specific, identifiable skills that can be measured - and learned. With a clear understanding of Executive Intelligence, managers can develop a means to improve their own performance as well as identify and cultivate the critical mass of talent their organizations so desperately seek. - Inside cover.
Introduction: The Unmistakable Signs of a Rising Star -- The Beginning -- What Every Business Needs -- Where Things Went Wrong -- What Is Executive Intelligence-An Overview -- Making the Invisible Visible -- Executive Intelligence in Real Life -- Executive Intelligence Explains Business Smarts -- Critical Thinking-The Foundation of Executive Intelligence -- Critical Thinking Applied to Business -- Discovering Executive Intelligence -- The Broad Reach of Executive Intelligence -- The Competitive Advantage: Why Certain People Make the Difference -- It Takes One to Know One -- Beyond Ideas: How Great Results Happen -- Why Is Executive Intelligence So Rare? -- The Executive Intelligence Gap -- No Time to Think-The Myth About Speed -- Action Without Thought-The Reality of Executive Behavior -- Blame It on the Brain -- Connectionism -- Common Errors of Business Judgment -- Intelligence Is the Key -- Beyond Academic Intelligence -- How Intelligence Measures Are Created -- The Changing Notions of Intelligence -- IQ Tests and Managerial Work -- Creating an Appropriate Executive IQ Test -- Taking a Wrong Turn -- The Charisma Trap -- A Cult of Personality -- Style and Personality: The Ongoing Distraction -- The Cycle of Indirect Measures-A Revolving Door -- The Evolution of the Job Interview -- A Step in the Right Direction -- The Limits of Past Behavioral Interviews (PBIs) -- The Mystery of Past Behavioral Interviews -- What Do PBIs Actually Measure? -- The Difference Between Knowledge and Intelligence -- How Does One Measure Intelligence? -- Test Format-A Crucial Ingredient -- How Do You Measure Executive Intelligence? -- Distinguishing Excellence -- Executive Intelligence-A Powerful, Validated Theory -- Teaching and Developing Executive Intelligence -- Valuing Executive Intelligence.
Includes bibliographical references (pages 285-293) and index.
Keywords: Executive ability; Executives -- Psychology; Leadership; 2; Executive ability; Executives -- Psychology; Leadership